Enhanced Electrochemical CO2 Reduction Using Nonthermal Plasma: Insights into Pd Catalyst Reactivation and Precise Control of H2O2 for Improved CO2 Reduction Reaction Activity - Jie Hu; Fuqiang Liu (Advanced Energy & Sustainability Research)
This study investigates the electrochemical reduction of CO2 on Pd/C with in situ‐generated H2O2 through low‐temperature nonthermal plasma. Catalyst deactivation, a common challenge in CO2 conversion, is addressed by leveraging the oxidizing environment created by H2O2. Experimental studies using linear sweep voltammetry and cyclic voltammetry demonstrate significantly improved CO2 reduction activity during plasma discharge, correlated with an enlarged hydrogen desorption peak. Multicomponent physics‐based computational simulation highlights the role of H2O2, a long‐lived species, in enhancing CO2 reduction. Formic acid is identified as a major liquid product, validated by nuclear magnetic resonance. The presence of H2O2 prevents CO poisoning on Pd surfaces, and H2O2 electroreduction alters hydrogen sorption, potentially creating an active PdHx phase for effective CO2 reduction. The study demonstrates the precise control of H2O2 concentration through nonthermal plasma, offering insights into Pd catalyst reactivation and improved CO2 reduction activity. These findings contribute to the understanding of electrochemical CO2 reduction mechanisms and provide a basis for optimizing catalytic processes in the presence of H2O2.